Применение биматричных игр в гармонизации ценностей стейкхолдеров проекта - Григорян, Тигран Георгиевич (НТУ "ХПИ", 2017)
Сформулирована задача гармонизации ценностей стейкхолдеров, как решение некоалиционной игры между двумя игроками – командой проекта во главе с менеджером и группами стейкхолдеров, объединенных сходными интересами. Предложены понятия операции балансировки ценности и гармонизации ценностей, а также представлена модель, интегрирующая данные понятия на основе применения биматричных игр. Предложены варианты типовых стратегий для игроков, что позволяет типизировать ситуации в реальных проектах.

The problem of project stakeholders interests harmonization is described. The problem of project stakeholders interests harmonization, as a solution of the noncooperative game between two players – the project team led by a manager and stakeholders, grouped by similar interests, is stated. The concept of the operation of the value balancing and the harmonization of values and the model integrating these concepts on the basis of bimatrix games are presented. The connection between the application of the proposed model with the project, product and value life cycle is showed. The developed model allows obtaining the probabilities of the use of recommended strategies taking into account stakeholders' value guidelines to ensure the sustainability of the project, necessary for its implementation and finalization. The alternatives for the typical players' strategies, allowing to typify situations in real projects and reduce the diversity of possible situations in value-oriented stakeholder' values balancing to a finite set of combination of enough low power are presented. The conclusions about the use of the proposed model obtained results and further research tasks have been made.
The Application of Bimatrix Games in the Harmonization of Project Stakeholders' Values
Keywords: управление проектами; ценность; стейкхолдеры; гармонизация; биматричные игры; project management; value; stakeholders; harmonization; bimatrix games